Confronting stresses affecting olive cultivation from the holobiont perspective - Cardoni, Martina; Mercado-Blanco, Jesús (Frontiers in Plant Science, 2023)
The holobiont concept has revolutionized our understanding of plant-associated microbiomes and their significance for the development, fitness, growth and resilience of their host plants. The olive tree holds an iconic status within the Mediterranean Basin. Innovative changes introduced in olive cropping systems, driven by the increasing demand of its derived products, are not only modifying the traditional landscape of this relevant commodity but may also imply that either traditional or emerging stresses can affect it in ways yet to be thoroughly investigated. Incomplete information is currently available about the impact of abiotic and biotic pressures on the olive holobiont, what includes the specific features of its associated microbiome in relation to the host’s structural, chemical, genetic and physiological traits. This comprehensive review consolidates the existing knowledge about stress factors affecting olive cultivation and compiles the information available of the microbiota associated with different olive tissues and organs. We aim to offer, based on the existing evidence, an insightful perspective of diverse stressing factors that may disturb the structure, composition and network interactions of the olive-associated microbial communities, underscoring the importance to adopt a more holistic methodology. The identification of knowledge gaps emphasizes the need for multilevel research approaches and to consider the holobiont conceptual framework in future investigations. By doing so, more powerful tools to promote olive’s health, productivity and resilience can be envisaged. These tools may assist in the designing of more sustainable agronomic practices and novel breeding strategies to effectively face evolving environmental challenges and the growing demand of high quality food products.